Sociopragmatic Study on Instagram Captions as a Media for Tourism Promotion in Bangkalan - Tri Pujiati; Meria Zakiyah Alfisuma; Arjulayana Arjulayana (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
This research was conducted as a form of investigation to see the pragmatic force on instagram captions containing information about tourism object in Bangkalan, Madura. This research using a qualitative descriptive as an effort to see the pragmatic force of instagram captions based on 3 indicators, attracting attention, the using of language on instagram caption, and increasing desire to visit tourism object. The data in this research found on instagram @adindarigama and @alfisuma. This research uses a questionnaire as a data collection tool. There are 100 respondents in this study. The theoretical approach used in this research is a sociopragmatic approach to see respondents’ perceptions regarding the pragmatic force of instagram captions which are used as the object of study. The results of the research show that (1) on pragmatic force with variable “attracting attention”, an average of 77, 75% agree that information on IG caption attracted attention; (2) on pragmatic power with the variable “use of language on IG captions”, an average of 72% agreed that the language content on IG captions was good; (3) on pragmatic force with the indicator “growing desire”, an average of 73, 3% agreed that the language on IG captions could increase the desire to visit tourism object in Bangkalan. The implication of this research is that the use of clear, concise, concise, interesting, and informative speech on instagram captions can be used as reference for providing information and education related to tourism in Bangkalan, Madura.